Creating a comprehensive information literacy plan : - Burkhardt, Joanna M. (Neal-Schuman Publishers Inc., 2005)
In college and university libraries across the nation, information literacy has become more than just an area of instruction--it has become part of the core mission of the organization. This step-by-step guide is designed to show academic library managers, instructors, and staff how to create a synthesized information literacy plan. The authors offer guidance about how to decide what to teach, when and how to deliver instruction, how to assess outcomes, and revise based on assessment results